"What I Would Do to Take Away Your Pain": A Photovoice Project Conducted by Mothers of Children With Medical Complexity. (February 2023) - Sonsteng-Person, Melanie; García-Pérez, Javier; Copeland, Victoria; Liévano-Karim, Laura; Abrams, Darlene; Jarman, Brittany; Marquardt, Rachel; Taitingfong, Sara; Van Leeuwen, Jesse; Valdez, Riahannon
Research identifies that families of children with medical complexities in the United States have diverse and complex needs. Despite research emphasizing that families demonstrate higher needs that are not being met, limited research focuses solely on mothers of children with medical complexities. Specifically, how mothers understand and identify themselves, understand and define their role in coordinating care, and how they view their own mental and physical health. As such, this study provides a better understanding of how mothers in San Diego, CA, navigate the day-to-day psychological, social, and physical realities of having a child with medical complexities. Through the use of the participatory action research method photovoice, mothers conducted a critical analysis of their daily lives. Findings identify mothers' main concerns about the conditions of their lives as well as the strengths they employ to care for themselves and their children successfully. Implications provide recommendations for hospitals working with mothers of children with medical complexities.